Clinical outcomes according to ECG presentations in infarct-related cardiogenic shock in the culprit lesion only PCI vs multivessel PCI in cardiogenic shock trial - Zeitouni, Michel; Akın, Ibrahim; Desch, Steffen; Barthélémy, Olivier; Brugier, Delphine; Collet, Jean-Philippe; de Waha-Thiele, Suzanne; Greenwood, John P.; Guedeney, Paul; Hage, Georges; Hauguel-Moreau, Marie; Huber, Kurt; et al. (Chest, 2021)
Background - The impact of ECG presentations of acute myocardial infarction (AMI) in cardiogenic shock is unknown. - Research Question - In myocardial infarction with cardiogenic shock, is there a difference in the outcomes and effect of revascularization strategies between non-ST-segment elevation myocardial infarction (NSTEMI) and left bundle branch block myocardial infarction (LBBBMI) vs ST-segment elevation myocardial infarction (STEMI)? - Study Design and Methods - Cardiogenic shock patients from the CULPRIT-SHOCK trial with NSTEMI or LBBBMI were compared with STEMI patients for 30-day and 1-year all-cause mortality. The interaction between ECG presentation and the effect of revascularization strategies on outcomes was evaluated. - Results - Of 665 cardiogenic shock patients analyzed, 55.9% demonstrated STEMI, 29.3% demonstrated NSTEMI, and 14.7% demonstrated LBBBMI. Patients differed in mean age (68.0 years in STEMI patients, 71.0 years in NSTEMI patients, and 73.5 years in LBBBMI patients; P = .015), cardiovascular risk factors, and angiographic severity. No difference was found in the 30-day risk of death between NSTEMI and STEMI patients (48.7% vs 43.0%; adjusted OR [aOR], 1.05; 95% CI, 0.66-1.67; P = .85), nor between LBBBMI and STEMI patients (59.2% vs 43.0%; aOR, 1.31; 95% CI, 0.73-2.34; P = .36). Although the univariate risk of death by 1 year was higher in NSTEMI and LBBBMI patients compared with STEMI patients, ECG presentation was not an independent risk factor of mortality after adjustment (NSTEMI vs STEMI: 56.4% vs 46.8%; aOR, 1.21; 95% CI, 0.76-1.92; P = .42; LBBBMI vs STEMI: 69.4% vs 46.8%; aOR, 1.59; 95% CI, 0.89-2.84; P = .12). ECG presentation did not modify the effect of the revascularization strategy on 30-day and 1-year mortality (P = .91 and P = .97 for interaction). - Interpretation - In patients with cardiogenic shock, NSTEMI and LBBBMI presentations reflect higher-risk profiles than STEMI presentations, but are not independent risk factors of mortality. ECG presentations did not modify the treatment effect, supporting culprit-lesion-only percutaneous coronary intervention as the preferred strategy across the AMI spectrum.